Lifetime prevalence of owner-reported medical conditions in the 25 most common dog breeds in the Dog Aging Project pack - Forsyth, Kiersten K.; McCoy, Brianah M.; Schmid, Sarah M.; Promislow, Daniel E. L.; Snyder-Mackler, Noah; , the DAP Consortium; Akey, Joshua M.; Benton, Brooke; Borenstein, Elhanan; Castelhano, Marta G.; Coleman, Amanda E.; Creevy, Kate E.; et al. (Frontiers in Veterinary Science, 2023)
Large scale data on the prevalence of diverse medical conditions among various dog breeds in the United States are sparse. This cross-sectional study sought to estimate the lifetime prevalence of medical conditions among US dogs in the US and to determine whether purebred dogs have a higher lifetime prevalence of specific medical conditions compared to mixed-breed dogs. Using ownerreported survey data collected through the Dog Aging Project (DAP) Health and Life Experience Survey for 27,541 companion dogs, we identified the ten most commonly reported medical conditions in each of the 25 most common dog breeds within the DAP cohort. Lifetime prevalence estimates of these medical conditions were compared between mixed-breed and purebred populations. The frequency of dogs for whom no medical conditions were reported was also assessed within each breed and the overall mixed-breed and purebred populations. A total of 53 medical conditions made upcomprised the top ten conditions for the 25 most popular breeds. The number of dogs for whom no medical conditions were reported was significantly different (p = 0.002) between purebred (22.3%) and mixed-breed dogs (20.7%). The medical conditions most frequently reported within the top ten conditions across breeds were dental calculus (in 24 out of 25 breeds), dog bite (23/25), extracted teeth (21/25), osteoarthritis (15/25), and Giardia (15/25). Overall, dental disease conditions and dog bites are common across breeds, including both large and small breed dogs. Purebred dogs in the DAP did not show higher lifetime prevalence of medical conditions compared to mixed-breed dogs, and a higher proportion of purebred dogs than mixed-breed dogs had no ownerreported medical conditions. However, iIndividual breeds may still show higher lifetime prevalence for specific conditions.